Pengaruh Kinerja Keuangan, Tingkat Pendidikan Dan Kemampuan Manajemen Pemilik Terhadap Pertumbuhan UMKM Di Kabupaten Sidoarjo - Imam Syafi'i; Susanti Susanti; Harti Harti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effect of financial performance, education level and owner management ability on the growth of micro MSMEs in leather handicrafts, bags, shoes and sandals in Sidoarjo Regency. This type of research is a purposive sampling research with a quantitative approach. The population in this study is the owner or perpetrator of micro UMKM in leather, bags, shoes and sandals in Sidoarjo Regency with a sample of 203 respondents. Data collection techniques using questionnaires and documentation. The data analysis technique used is multiple linear regression analysis with SPSS version 26 program tools. In the results of the study it was found that each of the independent variables included in this study financial performance, level of education and management ability of the owner partially or simultaneously had a positive and significant effect on the growth of micro SMEs in leather bags, shoes and sandals in Sidoarjo Regency. Keywords: Financial Performance, Owner's Education Level, Owner's Management Ability, MSME Growth